2001
DOI: 10.1111/j.1572-0241.2001.04132.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' values for health states associated with hepatitis c and physicians' estimates of those values

Abstract: There was little agreement between patients' preference values about hepatitis C and their physicians' estimates of those values. Utility analysis could facilitate shared decision making about hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…Yet, existing evidence suggests that providers underestimate the relative importance of side effects and other aspects of HCV treatment to patients. [7,31,32] To our knowledge, this is the first quantitative assessment of patients’ preferences for the likely features of what may soon become the dominant treatment for chronic HCV infection: peginterferon plus ribavirin plus a DAA.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, existing evidence suggests that providers underestimate the relative importance of side effects and other aspects of HCV treatment to patients. [7,31,32] To our knowledge, this is the first quantitative assessment of patients’ preferences for the likely features of what may soon become the dominant treatment for chronic HCV infection: peginterferon plus ribavirin plus a DAA.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians aware of the availability of HCV treatment tended to overestimate the efficacy of interferon and ribavirin therapy, citing response rates in up to 70% [19,22]. In two studies, healthcare providers expressed significant concerns about adverse effects of antiviral therapy, which largely mirrored patient responses [28,30]. In one study, physicians indicated a willingness to suggest treatment if response rates exceeded 60% [37].…”
Section: Treatmentmentioning
confidence: 98%
“…Using a visual analogue scale to rate the impact of hepatitis C and its treatment on health states, physicians rated disease-related symptoms and severity (i.e., presence of cirrhosis) as significantly detrimental, with mild symptoms or the presence of asymptomatic cirrhosis being perceived as less negative than the side effects of antiviral treatment [37]. Using a similar approach, Cotler et al compared attitudes of patients with those of their treating physicians [30]. While physicians tended to underestimate the impact of mild disease, they overestimated the potential negative effect of cirrhosis and/or advanced disease on patients.…”
Section: Provider Attitudesmentioning
confidence: 98%
See 2 more Smart Citations